Հռոմի Բենեդիկտոս ԺԵ. Պապը եւ Հայոց Մեծ Եղեռնը - Վահագ Հարությունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматриваются действия Ватикана и самого Папы Бенедикта XV в годы Геноцида армян. Используя архивные материалы, публикации и исследования в области истории Католической Церкви и европейской политики XX века, автор излагает детальную картину событий 1914-1922 годов, подчеркивается, что с самого начала военных действий Ватикан и Папа Бенедикт XV в частности решительно осуждали массовою резню армян и применение военной силы против мирного населения. The article discusses the policy of the Vatican and of Pope Benedict XV, who was the leader of the Catholic Church in the years of the Armenian Genocide. Based on archive documents, publications and scientific researches in the field of history of the Catholic Church and European policy of the 20th century, the author creates a detailed picture of events that took place between 1914-1922. It is highlighted that from the very beginning of military operations the Vatican and Pope Benedict in particular strongly condemned the massacre of the Armenians and the use of military forces against peaceful civilians.
Keywords: History; Armenian church; Armenian Diaspora; Christianity